PERSPEKTIF NEGARA BERKEMBANG PADA HAK KEKAYAAN INTELEKTUAL DAN TRANSFER TEKNOLOGI - Santyaningtyas, Ayu Citra (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The exploitation of the use of technological knowledge is at the heart of the development process. Developing countries usually acquire knowledge from developed countries rather than creating it themselves. The process of acquiring knowledge and technology is carried out by means of technology transfer, namely by transferring patents for certain products. In this paper the author will explain the meaning of technology transfer and its various types. It also addresses situations where there is a loss of confidentiality and elaborates on the effect this has on the obligations of parties to contracts in various jurisdictions. This article uses sociological juridical research methods and in this article also tries to deal with various intellectual property issues involved in technology transfer and tries to analyze things from the perspective of developing countries.